Exploring quantum microwave radiation emitted from superconducting electronic circuits - Eichler, Christopher (2013)
Superconducting electronic circuits have turned into one of the prime physical systems to investigate quantum optical and atomic physics phenomena in engineered solid state devices. While the on-demand generation and the processing of quantum states on a chip are now routinely achieved with high fidelity, it remains challenging to detect propagating microwave photons with equally high efficiency. This is mainly due to the absence of efficient photon counters in this frequency range. In my presentation, I explain how we employ low-noise linear amplifiers instead of photon counters for measuring microwave field correlations at the quantum level. For this purpose we have developed efficient data acquisition, processing and analysis techniques to separate the quantum signal of interest from the noise added by the amplifiers [1]. In our experiments we have successfully generated and characterized various types of interesting quantum fields, ranging from on-demand single photons [2], over squeezed radiation [3], to spatially entangled fields [4]. Recently, we have also developed our own parametric amplifiers to perform nearly quantum limited measurements of microwave radiation [3,6]. These enabled us to observe entanglement between a quantum two-level system and microwave photons propagating freely through a transmission line [5]. The possibility to accurately synthesize, guide and characterize non-classical microwave fields bears great potential to be used in radiation based quantum simulation and quantum network architectures and for probing other systems with yet unrivaled sensitivity. References: [1] C. Eichler et al., PRA 86, 032106–13 (2012), [2] C. Eichler et al., PRL. 106, 220503 (2011), [3] C. Eichler et al., PRL 107, 113601 (2011), [4] C. Lang et al. Nat. Phys., in print (2013), [5] C. Eichler et al., PRL. 109, 240501 (2012), [6] C. Eichler and Wallraff, A., arXiv:1305.6583
Keywords: wwwqudev